Determination of the relationship of the spiritual orientation of nurses with compassion fatigue, burnout, and compassion satisfaction - Polat, Hatice; Turan, Gulcan B.; Tan, Mehtap (Wiley, 2020)
Purpose This study aimed to determine the relationship of the spiritual orientation of nurses with compassion fatigue, burnout, and compassion satisfaction of nurses working in two large hospitals. Design and Methods This was a descriptive relational study conducted in Ataturk University Research Hospital between April and September 2016. Data were collected from 379 volunteer nurses using the convenience sampling method. A questionnaire, Professional Quality of Life Scale (ProQOL) R-IV and Spiritual Orientation Inventory (SOI) were used to collect the research data. Findings It was found that 55.7% of nurses were aged 18 to 27 years, 74.1% of nurses were females. The professional satisfaction of the nurses was high, with low rates of burnout and compassion fatigue. The spiritual orientation of the nurses was high according to the average SOI total score (98.83 +/- 15.04). The mean score for compassion fatigue was 21.50 +/- 8.69, and the mean score for compassion satisfaction was 34.10 +/- 9.91. The mean score for burnout was 19.83 +/- 6.39. Practice Implications Nurses' compassion fatigue, burnout and compassion satisfaction should be evaluated regularly. The results revealed no correlation between spiritual orientation and these parameters. Studies investigating compassion fatigue among nurses should question the time nurses spend on themselves and leisure time.
Keywords: burnout; compassion fatigue; nurse; satisfaction; spirituality